EFEKTIVITAS PERENCANAAN PAJAK AKHIR TAHUN DALAM MENGURANGI RISIKO PEMERIKSAAN PAJAK - Hendrico, Hendrico; Aripin, Aripin; Pahala, Indra; Wahono, Puji (Penerbit Lafadz Jaya, 2025)
This study aims to examine the effectiveness of year-end tax planning in reducing the risk of tax audits. Strategically and legally implemented tax planning at the end of the fiscal year is believed to be an effective tool to minimize potential corrections and findings by tax authorities. This research employs a qualitative approach using a library research method. The data used are secondary sources obtained from scientific journals, books, articles, and official documents related to tax planning and tax audits. The data were analyzed descriptively, emphasizing interpretation and synthesis of previous research findings. The results indicate that year-end tax planning, when conducted in compliance with applicable tax regulations, can provide significant benefits for taxpayers—both in terms of tax burden efficiency and audit risk mitigation. Such planning includes strategies like income equalization, optimal utilization of fiscal incentives, and accurate and well-documented reporting. Furthermore, previous studies highlight that understanding tax regulations and the readiness of corporate tax administration are critical factors in supporting the effectiveness of tax planning. Therefore, this study underscores the importance of year-end tax planning as a proactive and strategic form of tax compliance, as well as a preventive measure against potential audit risks by tax authorities.